2011
DOI: 10.3171/2011.1.spine10571
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of perioperative surgical site infection after minimally invasive versus open posterior/transforaminal lumbar interbody fusion: analysis of hospital billing and discharge data from 5170 patients

Abstract: Object Surgical site infection (SSI) after lumbar fusion results in significant patient morbidity and associated medical resource utilization. Minimally invasive (MI) techniques for posterior/transforaminal lumbar interbody fusion (P/TLIF) were introduced with the goals of smaller wounds, less tissue trauma, reduced blood loss, and quicker postoperative recovery, while maintaining comparable surgical results. Studies with sufficient power to directly compare the inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 32 publications
1
100
1
Order By: Relevance
“…Data in the present study are consistent with those in previous reports evaluating minimally invasive techniques. 20,26,28,38 In a retrospective study using an administrative database, McGirt and colleagues 20 reported that their minimally invasive technique was associated with a decrease in the incidence of SSI following 2-level posterior/transforaminal lumbar interbody fusion. O'Toole and colleagues postulated several possible reasons for the lower risk of SSI associated with minimally invasive surgery: reduced exposure of deep tissue, preventive effect of a tubular retractor for local contamination, smaller incisions, and reduced dead space in the surgical site after closure.…”
Section: Discussionmentioning
confidence: 99%
“…Data in the present study are consistent with those in previous reports evaluating minimally invasive techniques. 20,26,28,38 In a retrospective study using an administrative database, McGirt and colleagues 20 reported that their minimally invasive technique was associated with a decrease in the incidence of SSI following 2-level posterior/transforaminal lumbar interbody fusion. O'Toole and colleagues postulated several possible reasons for the lower risk of SSI associated with minimally invasive surgery: reduced exposure of deep tissue, preventive effect of a tubular retractor for local contamination, smaller incisions, and reduced dead space in the surgical site after closure.…”
Section: Discussionmentioning
confidence: 99%
“…The potential advantages of converting a minimally invasive TLIF to a surgery performed under fully endoscopic visualization include a smaller incision, decreased blood loss, shorter patient recovery time, and the possibility of performing the surgery without general anesthesia. 5,8,[11][12][13] The significant anatomical feature of the lumbar neural foramen that makes endoscopic TLIF a challenge is the small working area between the traversing and exiting roots through which 1) a large amount of facet bone and disc material must be removed to achieve satisfactory nerve decompression, 2) sufficient endplate preparation…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The minimally invasive TLIF procedure has been recently shown to reduce morbidity and health care costs in comparison with open TLIF. 5,8,10,11,14 We set out to evaluate the relevant anatomy at the neural foramen in consideration for the development of an interbody fusion device, appropriate instruments for neural decompression, and OBjEcTIVE The authors describe a cadaveric analysis to determine the ideal dimensions and trajectory for considering endoscopic transforaminal interbody implantation. mEThOdS The soft tissues of 8 human cadavers were removed from L-1 to the sacrum, exposing the posterior bony elements.…”
mentioning
confidence: 99%
“…The advent of minimally invasive spine surgery (MIS) has been well applied to instrumentation constructs through most of the spinal axis with good results, allowing patients to have smaller incisions, less blood loss, shorter hospital stays, decreased rates of infections, and subsequent cost benefits [4][5][6]. Advocates of these techniques suggest that these factors lead to earlier mobilization and rehabilitation and decreased morbidity from being immobilized.…”
Section: Introductionmentioning
confidence: 99%